PREVALENCE AND RISK FACTORS OF DIABETES MELLITUS AMONG WOMEN USING THE MULTINOMIAL LOGISTIC REGRESSION MODEL - Olayeye, Teniola O.; Bodunwa, Oluwatoyin K.; Adewole, Ayoade I. (FUDMA JOURNAL OF SCIENCES, 2024)
Diabetes mellitus (DM) is a prolonged disease with debilitating effect on man. This includes many health problems because the disease is a risk factor for a number of complications. This study employs a multinomial logistic regression model to explore the prevalence of diabetes and identify contributing factors. Analyzing a diverse range of variables, the study aims to provide in-depth insights into the complex relationships influencing diabetes occurrence. The findings indicated that poor health status contributed more, among other factors, in terms of influencing diabetes. This could be as a result of having other health challenges. Also, women with stroke, high blood pressure, high cholesterol and heart disease were at greater risk of having diabetes compared to those not having. Women who were active had lower risk of having diabetes compared to those who were inactive as physical activities help control bodyweight through increased fat metabolism. Increasing age is often accompanied by a progressive decline in most physiological functions, resulting in increased susceptibility to disease. It was observed in this research that DM was more prevalent in elderly women than women of younger age.